Mengukur Dampak Adopsi Payment Gateway Terhadap Loyalitas Pelanggan Dan Peningkatan Volume Transaksi UMKM - Bayu Aditya Nuryansyah; Raihanullah; Oriandika Rasyid Rasyid (Journal of Information Systems and Business Technology, 2025)
This study aims to measure the impact of payment gateway adoption on customer loyalty and transaction volume growth in Micro, Small, and Medium Enterprises (MSMEs). Digital transformation has encouraged MSMEs to adapt to modern payment systems, including e-wallets, virtual accounts, and debit/credit cards. This study uses a quantitative method by distributing questionnaires to 120 MSME players in urban and semi-urban areas. Data analysis was performed using Path Analysis to test the direct and indirect relationships between the variables of perceived ease of use, trust, and satisfaction with the variables of customer loyalty and increased transaction volume. The results show that the adoption of payment gateways has a significant positive effect on customer loyalty (p < 0.05) and MSME transaction volume. The trust factor has the greatest contribution in encouraging customers to make repeat transactions. This study confirms that payment digitization can be an effective strategy for MSMEs in improving business performance. The implications of this study can be used as a basis for MSMEs and payment gateway service providers in improving service quality and transaction features.